Assessment of Railway Station Modernisation Combining Risk Analysis with Multi-Criteria Analysis - Javorik, Tomas; Tyfa, Lukas (Communications - Scientific Letters of the University of Zilina, 2015)
When modernising train stations, several options are usually available for the layout of the tracks and its parameters. The best option is chosen by assessing different criteria; it is not an exact procedure, but a compromise between often different perspectives. Many methods are available to aid the decision-making process in these situations; the authors of this article apply mutually combined multi-criteria and qualitative risk analysis to assess two self-proposed options for the modernisation of the Bakov nad Jizerou station (situated in Central Bohemia in the Czech Republic).
Keywords: railway station; railway modernisation; risk analysis; multi-criteria analysis